The Politics of Attachment: Lines of Flight with Bowlby, Deleuze and Guattari. (December 2015) - Duschinsky, Robbie; Greco, Monica; Solomon, Judith
Research on attachment is widely regarded in sociology and feminist scholarship as politically conservative – oriented by a concern to police families, pathologize mothers and emphasize psychological at the expense of socio-economic factors. These critiques have presented attachment theory as constructing biological imperatives to naturalize contingent, social demands. We propose that a more effective critique of the politically conservative uses of attachment theory is offered by engaging with the 'attachment system' at the level of ontology. In developing this argument we draw on Deleuze and Guattari, making use of the common language of ethology which links their ideas to that of attachment theory. The attachment system can and has been reified into an image of the infant returning to their caregiver as an image of familial sufficiency. This has offered ammunition for discourses and institutions which isolate women from health, social and political resources. Yet Deleuze and Guattari can help attachment theory and research to be recognized as a powerful ally for progressive politics, for reflection on the movement of human individuation, and for arguing for the meaningful resourcing of those who care for someone else.